Oxidative stress and temporomandibular joint disorders - Yoshiaki Kawai; Masaichi-; Eiro Kubota (Elsevier, 2008)
Etiology of temporomandibular joint disorders (TMD) was estimated as excessive mechanical stresses inflicted on the temporomandibular joint (TMJ). The stresses including bruxism, clenching and oral parafunctional habits in daily life cause irreversible damage in the joint tissue. As the stress loading to the TMJ, it has been shown that increase of generation of free radicals, biosyntheses of arachidonic acid catabolite, release of neuropeptide and cytokines, and activation of matrix degrading enzymes from various TMJ tissues were observed. Few studies of reactive oxygen species (ROS) in TMD were reported. The authors postulate mechanisms that provably involved in the production of ROS in the TMJ and the subsequent induction of molecular events that may amplify damage to the joint tissues.